Method for a homogeneous distribution of pollens in an environmental exposure chamber. Issue 9 (1st June 2016) - Kenney, P.; Bønløkke, J.; Hilberg, O.; Ravn, P.; Schlünssen, V.; Sigsgaard, T.
Summary: Background: A variety of different environmental exposure chambers (EECs) have been used to evaluate treatments for allergic rhinitis. Objective: To describe and test a system for a homogenous distribution of grass pollen, Phleum Pratense, in an EEC to be used for controlled pollen exposure studies in allergic participants. Methods: A chamber made of stainless steel with completely rounded corners, seating four individuals at a time, was used. Room pressure, temperature, humidity and the air change rate were kept constant throughout the study period. A rotating pipette dispensed a uniform supply of pollen into a turntable's v‐shaped grooves. A stainless steel capillary tube sucked the pollens into a venturi throat at which time the pollens were mixed with a high‐pressure airstream of compressed high‐efficiency particulate arrestance filtered air and then transported to a spreading plate inside the EEC. To achieve uniform concentrations in the EEC, the turntable's rotating speed was continuously adjusted using information from video‐coupled feedback and feed forward mechanisms. Pollen levels were detected using standard volumetric air samplers and laser particle counters. The target pollen exposure level was 1000 pollens/m 3 . Twenty‐one participants were exposed to pollens in the EEC twice for 210 min. Participants evaluated their symptoms every 30 min using a total nasal symptom score (TNSS) consisting of blocked nose, runny nose, nasal itching and sneezing. Results: Across fifteen study days, the average pollen level was 982 pollens/m 3 (SD, 102 pollens/m 3 ). On average, participants experienced a 10% difference in overall pollen levels between their two visits to the EEC. The mean TNSSs rose throughout the exposure period, with a low at baseline of 0.43 (SD, 0.68) to a high of 4.71 (SD, 2.43) just before exiting the EEC. Conclusion and Clinical Relevance: This EEC provides a reproducible, precise and homogenous distribution of pollens making it suitable for single‐centre allergy clinical trials.